PERSEPSI ORANG TUA ANAK BERKEBUTUHAN KHUSUS PADA SEKOLAH LUAR BIASA NEGERI (SLBN) KUANTAN SINGINGI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Yanti, Asvira Pamelda; Zahirman, Zahirman; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This research is motivated by complaints felt by parents ofchildrend with spcial needs who send their children to school in SLBN KuantanSingingi. This study aims to determine the perceptions of parents of children with special needs at the Kuantan Singingi Special School (SLBN), Kuantan Tengah District, Kuantan Singingi District. This research uses a qualitative approach. The informants who were examined by using purposive sampling technique were parents of children with special needs in SLBN Kuantan Singingi. Data collection techniques used were observation, interviews, and data analysis. Based on the results of research conducted, it can be concluded that the perception of parents at SLBN Kuantan Singingi is not good. Because the goals of the special school have not yet been achieved, incomplete and inadequate infrastructure and the lack of teachers to teach.Key Words: Perception, Parents, Children With Special Needs, Special School